2007
DOI: 10.1002/joc.1491
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling of current and future rainfall climatologies for southern Morocco. Part I: Downscaling method and current climatology

Abstract: Abstract:The use of a statistical-dynamical downscaling approach to obtain a high-resolution rainfall climatology for a subtropical region in southern Morocco is analysed. The statistical part of the downscaling uses Circulation Weather Types (CWTs) as a measure for near-surface wind fields calculated from sea-level pressure (SLP) data. The daily CWTs are correlated with daily rainfall data at three different climate stations in the region for the period 1978-1997 and systematic differences are discussed. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Several authors have shown the impact of the NAO index on precipitation in particular for the Atlantic part of Morocco (El Hamly and Sebbari, 1998;Knippertz et al, 2003, Huebener andKerschgens, 2007a). However Knippertz et al (2003) indicate a lower correlation with the NAO index in the Mediterranean region, more influenced by local mechanisms and by the Mediterranean cyclonic activity.…”
Section: Stations and Climatic Datamentioning
confidence: 91%
See 1 more Smart Citation
“…Several authors have shown the impact of the NAO index on precipitation in particular for the Atlantic part of Morocco (El Hamly and Sebbari, 1998;Knippertz et al, 2003, Huebener andKerschgens, 2007a). However Knippertz et al (2003) indicate a lower correlation with the NAO index in the Mediterranean region, more influenced by local mechanisms and by the Mediterranean cyclonic activity.…”
Section: Stations and Climatic Datamentioning
confidence: 91%
“…However, they observed a bad representation of the influence of mountainous areas in the GCM. Together with Huebener and Kerschgens (2007a), they recommended the use of downscaling approaches to better reproduce the climate of the center and southern parts of Morroco, highly influenced by orography. Driouech et al (2009) have shown the ability of the variable resolution ARPEGE climate model at a 50 km resolution to reproduce heavy rainfall and long dry periods in the center of Morocco.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial and temporal precipitation distributions are affected by the Atlantic Ocean, the Mediterranean Sea, and the Sahara and Atlas Mountains [65]. Several studies demonstrated strong correlations between inter-annual precipitation variability and the North Atlantic Oscillation (NAO), the Atlantic Multi-Decadal Oscillation (AMO), and the El Niño-Southern Oscillation (ENSO) indices [65][66][67][68]. Therefore, both local and large-scale factors impact the precipitation that is characterized by a strong irregularity in time and space.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Morocco by its geographical position dominated by the semi-arid bioclimatic zones (more than 85 % of cultivated areas) has shown signs of climate variability during the last decades (Huebener and Kerschgens, 2007). The extension of dry periods became a reality in this part of the globe.…”
Section: Introduction:-mentioning
confidence: 99%